The recommendations of the De Kock Commission of Inquiry and its implications for foreign security investments by South African residents - N. Bhana (South African Journal of Business Management, 1985)
South African investors have been precluded from investing in foreign securities by the Exchange Control Regulations of 1961. Furthermore, the monetary policy pursued by the authorities has resulted in an inefficient financial market. Investments on the capital market have not earned satisfactory real rates of return, and prices on the JSE appear to have been driven to artificial heights. The De Kock Commission of Inquiry has proposed several recommendations which will have far-reaching consequences for investors in South Africa. The proposal of market-related interest rates and the abolition of prescribed investments by institutional investors is likely to result in long-term securities earning substantially higher real rates of return. The relaxation of exchange control for both direct and portfolio investment is likely to stem the flow of funds into the JSE. Investment funds can be expected to flow between the JSE and the various foreign equity markets depending on the economic prospects in the different countries. The high foreign exchange cost and poor liquidity of the local exchange market has been an obstacle to investors in foreign securities. The creation of a larger and more efficient foreign exchange market is likely to facilitate international portfolio diversification in South Africa.
Keywords: 650